2008
DOI: 10.1176/appi.psychotherapy.2008.62.4.353
|View full text |Cite
|
Sign up to set email alerts
|

Multicultural Considerations for the Application of Attachment Theory

Abstract: Attachment styles impact relationships. Research illustrates the importance of attachment from infancy to adulthood across all cultures. The focus of this paper is to explore attachment theory within the context of the therapeutic process with the inclusion of multicultural implications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…Bartholomew and Horowitz [47], who suggested a different typology than Hazan and Shaver [40] for attachment styles, by including two types of avoidance, found that more men than women had ‘dismissing‐avoidant’ attachment styles, and more women classed themselves as 'fearful‐avoidant. Nonetheless, some researchers proposed that the gender differences in attachment are not universal, but rather, depend on cultural input even within the Western culture [48, 49]. We expected that more women cancer survivors would define themselves with a secure attachment style than men.…”
mentioning
confidence: 97%
“…Bartholomew and Horowitz [47], who suggested a different typology than Hazan and Shaver [40] for attachment styles, by including two types of avoidance, found that more men than women had ‘dismissing‐avoidant’ attachment styles, and more women classed themselves as 'fearful‐avoidant. Nonetheless, some researchers proposed that the gender differences in attachment are not universal, but rather, depend on cultural input even within the Western culture [48, 49]. We expected that more women cancer survivors would define themselves with a secure attachment style than men.…”
mentioning
confidence: 97%
“…6 In accordance with the present study, Brown et al studied the relationship between the child-rearing styles, attachment styles and worry in anxious children and found that the ambivalent insecure attachment style has more relationship with worry in comparison to secure attachment style. 15 Moreover, Cassidy et al observed that among the patients with GAD, the experience of lack of affection in childhood was more evident, and this group of children were more vulnerable in the relationship with their mothers in comparison to the subjects in the control group. 32 Although the influence of mother's sensitive response to the needs of growing child on the formation of secure attachment in children has been proven in many studies, today psychologists believe that both factors of the caregiver response to the child and the child temperament are important and decisive in the formation of secure attachment in children.…”
Section: Maudsley Obsessive-compulsive Inventory (Moci)mentioning
confidence: 99%
“…7 In the study by Brown et al it became clear that insecure ambivalent attachment style had greater relationship with worry in patients with GAD in comparison to secure attachment style. 15 Since major depression disorder (MDD), as a form of mood disorder, as well as obsessive-compulsive disorder (OCD) and GAD, as two forms of anxiety disorders, are among the most common mental disorders that people might face during their lifetime, a need is felt for knowing the etiology of the mentioned disorders and finding the factors that cause and support them.…”
mentioning
confidence: 99%
“…Bowlby's attachment theory is a good example [18,19]. But in the development and functioning of a human being no less important than the emotional aspects of the relationship with parents and other attachment figures are cognitive and linguistic processes, enabling to receive attachment.…”
Section: Towards Describing and Measuring Neurotic Personality Factorsmentioning
confidence: 99%